Beautify the blurry self: Low self‐concept clarity increases appearance management - Wang, Jiaqian; Yu, Yiqi (Journal of Consumer Psychology, 2023)
AbstractThe current research examines how and why self‐concept clarity (i.e., having self‐aspects that are integrated into a well‐defined whole) shapes consumers' appearance management behaviors. Five (including four pre‐registered) studies and one supplemental study provide correlational and causal evidence for the link between low self‐concept clarity and appearance management (e.g., choice of appearance‐enhancing products, interest in cosmetic procedures, and beauty filters). Furthermore, we demonstrate that public self‐consciousness mediates this effect (Studies 3–4). We also find convergent process‐by‐moderation evidence that low self‐concept clarity increases appearance management only when the appearance management behavior is perceived to be socially acceptable (Study 5). In addition, we rule out global and appearance self‐esteem, private self‐consciousness, self‐improvement, and mood management as potential mechanisms. This research extends the literature on self‐concept, impression management, and appearance management and yields implications for beauty marketing, health communication, and consumer well‐being.